An evaluation model of educational quality assurance at junior high schools - Sugiyanta Sugiyanta; Soenarto Soenarto (REID (Research and Evaluation in Education), 2016)
The study was to develop an appropriate evaluation model of quality assurance (QA) for evaluating the programs of the educational QA (EQA) at junior high schools. The study was a research and development study that referred to the steps developed by Borg and Gall. The results of the study show that the evaluation model of EQA in junior high schools consist of the implementation of QA system and the performance of QA. The constructs for the instrument of QA system implementation consisted of planning, implementation, monitoring and evaluation, and the act of revision is based on the exploratory factor analysis at the significance level of 0.000. The constructs for the instrument of EQA performance consisted of: resource development; program and activity development; participation, satisfaction, knowledge change, attitude change, and behavior change of school community; social, economic, and school environmental development based on the exploratory factor analysis at the significance level of 0.000. The feasibility of the evaluation model is in a good category based on  experts’, users’, and practitioners’ judgment and the evidence found in the field testing.